THE STUDY OF MONETARY BEHAVIOR IN THE CONTEXT OF PERSONAL TIME CONCEPTION AND TIME ORIENTATION - Hayrapetyan, D. R.; Amiraghyan , A. V. (Արդի հոգեբանություն, 2019)
Numerous studies are well-known in the field of behavioral economics which are aimed to explore the relationships between the psychological factors and the monetary behavior. However, a wide range of psychological aspects of financial management continues to remain unexplored, such as the interrelation of financial strategies, goals and plans with person’s time perspective, time preference and orientation. Our article is focused on a comprehensive study of person’s monetary and financial management strategies in the context of time conception and time orientation.